Analisis Penerapan Prinsip Syariah pada Produk Hasanah Card di Bank Syariah Indonesia KCP Cemara Asri - Askur Hamid Nasution; Nurul Inayah; Tuti Anggraini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to investigate the application of sharia principles in Hasanah Card products at Bank Syariah Indonesia KCP Cemara Asri. The background of the study includes the increasing market demand for banking products that comply with sharia principles. The research questions focus on the extent to which Bank Syariah Indonesia implements sharia principles in Hasanah Card products and how the market responds to its implementation. The research method uses a qualitative approach with interviews and document analysis. The provisional hypothesis shows that the implementation of sharia principles in Hasanah Card includes aspects of transparency, fairness, and sharia compliance. However, the adoption of this product still faces some challenges in terms of public understanding and acceptance of sharia features. The author concludes that while Bank Syariah Indonesia has taken sharia principles into account in the development of the Hasanah Card product, further efforts are needed to improve public understanding and acceptance and strengthen overall sharia compliance.